The natural history of weasels and stoats : ecology, behavior, and management - King, C. M. (Carolyn M.) (OUP E-Books., 2007)
Both kinds of knowledge are brought together - observations for the traditional naturalist and rigorous measurements and interpretations for modern scientists, integrated into a single, readable account. This edition provides a comprehensive summary of the extensive advances over the last 15 years.